أثر الائتمان المقدم للقطاع الخاص على النمو الاقتصادي في الجزائر- دراسة قياسية خلال الفترة1980-2022- - نعيمة بالخير (جامعة الوادي University Of Eloued, 2024)
"يعتبر الائتمان المصرفي أحد محركات التنمية الاقتصادية، ونقصه يشكل عقبة رئيسية أمام النمو الاقتصادي. ويُعد القطاع المصرفي من القطاعات الرائدة في الاقتصاد لأنه يلعب دور الوسيط في توفير التمويل اللازم للقطاعات الإنتاجية من خلال تعبئة المدخرات المحلية والخارجية وتمويل الاستثمارات التي تُعد محرك النشاط الاقتصادي. تبرز أهمية وفعالية القطاع المصرفي في قدرته على التوجيه الأمثل والكفء للتمويل المصرفي للقطاعات الاقتصادية المختلفة، وأهمها القطاع الخاص الذي يهيمن على نسبة كبيرة من النسيج الاقتصادي الوطني ويعتمد على الائتمان المقدم من وحدات القطاع المصرفي. بناءً على ذلك، قامت الجزائر بعدة إصلاحات اقتصادية وبرامج تنموية لتفعيل هذا القطاع وتطويره في ظل الانتقال إلى اقتصاد السوق. تم فحص أثر الائتمان المقدم للقطاع الخاص على النمو الاقتصادي خلال الفترة (1980-2022) باستخدام نموذج الانحدار الذاتي للإبطاء الزمني الموزع (ARDL). وقد شملت الدراسة خمس متغيرات، حيث يمثل المتغير التابع حصة الفرد من الناتج المحلي الإجمالي الحقيقي، بينما تمثل المتغيرات المستقلة الائتمان المقدم للقطاع الخاص نسبةً إلى الناتج المحلي الإجمالي، الإنفاق الاستهلاكي الحكومي النهائي، الانفتاح التجاري نسبةً إلى الناتج المحلي الإجمالي، والمطلوبات السائلة نسبةً إلى الناتج المحلي الإجمالي. هدفت الدراسة إلى نمذجة العلاقة بين الائتمان المقدم للقطاع الخاص والنمو الاقتصادي. أظهرت النتائج وجود علاقة توازنية طويلة الأجل بين هذه المتغيرات، وكان من أبرز النتائج وجود علاقة سلبية وغير معنوية إحصائيًا بين الائتمان المقدم للقطاع الخاص والنمو الاقتصادي في الجزائر على المدى الطويل، وغياب هذه العلاقة على المدى القصير. يُعزى ذلك إلى فشل القطاع المصرفي الجزائري في دعم القطاع الخاص بشكل فعال. بناءً على هذه النتائج، يُوصى بتعزيز البيئة الاقتصادية من خلال تحسين قوانين حقوق الملكية، مكافحة الفساد، تشجيع الاستثمار في التعليم وتكنولوجيا المعلومات، وتطوير البنوك والبنية المالية لتعزيز الشمول المالي والثقة في القطاع المصرفي. " "Bank credit is considered one of the drivers of economic development, and its scarcity represents a major obstacle to economic growth. The banking sector is one of the leading sectors in the economy, as it acts as an intermediary in providing the necessary financing for productive sectors by mobilizing and gathering local and foreign savings and financing investments, which are the driving force of economic activity. The importance and effectiveness of the banking sector lie in its ability to optimally and efficiently direct banking finance to various economic sectors, most notably the private sector, which dominates a large proportion of the national economic fabric and relies on credit provided by banking sector units. Consequently, Algeria has undertaken several economic reforms and development programs to activate and develop this sector in the transition to a market economy. The impact of credit provided to the private sector on economic growth during the period (1980-2022) was examined using the Autoregressive Distributed Lag (ARDL) model. Five variables were selected, with the dependent variable being the per capita share of real GDP, and the independent variables being credit provided to the private sector as a percentage of GDP, final government consumption expenditure, trade openness as a percentage of GDP, and liquid liabilities as a percentage of GDP. The study aimed to model the relationship between credit provided to the private sector and economic growth. The results indicated a long-term equilibrium relationship between these variables. Among the key findings was the existence of a negative and statistically insignificant relationship between credit provided to the private sector and economic growth in Algeria in the long term, with this relationship absent in the short term. This is attributed to the failure of the Algerian banking sector to effectively support the private sector. Based on these results, it is recommended to enhance the economic environment by improving property rights laws, combating corruption, encouraging investment in education and information technology, and developing banks and financial infrastructure to enhance financial inclusion and build confidence in the banking sector. "
مذكرة ماستر
Keywords: الائتمان المقدم للقطاع الخاص، الجزائر، النمو الاقتصادي، منهجية ARDL; Algeria; ARDL methodology; bank credit to the private sector; economic growth.